Implementasi Metode ODOA (One Day One Ayat) dalam Meningkatkan Kemampuan Menghafal al-Quran - Anwar , Khoirul; Hafiyana , Mufti (Jurnal Pendidikan Islam Indonesia, 2018)
Education has an important role in human life, without presence of human education will not develop properly. Implementation of education of children should be started early, especially religious education, because it will make strength of religion obtained. The duties of parents, teachers, and community is how guide of religion including in it teaches the al-Quran is still done, meaning that religious education should not be allowed to disappear. In order to maintain purity of Qur'an, in addition to do it by reading and understanding it, we also try to memorize it. At basic thought mentioned it, then formulated a focus on this research is planned memorizing activities of the al-Quran, the implementation of ODOA method (one day one ayat ) in improving the ability to memorize the al-Quran of students, and evaluation of memorizing activities of the al-Qur’an in Awar Awar NU Elementary School.